Selective neck dissection in adolescent on extracorporeal membrane oxygenation – the role of the anesthesiologist. Case report with review of the literature. - Ivana Bureš Valentić; Renata Curić Radivojević; Ivana Vukušić; Ozren Vugrinec; Filip Rubić (Liječnički vjesnik, 2022)
In almost 50 years since its first application extracorporeal life support has become an indispensable tool in the care of children and adults with severe heart and lung failure refractory to conservative treatment. Over the last decade, there has been a significant increase in the use of extracorporeal membrane oxygenation devices in patients of all ages. Greater availability of the device and improved technology have led to the expansion of indications for its use. A patient on extracorporeal life support may undergo emergency surgery or diagnostic and therapeutic procedures that require the presence of an anesthesiologist. Due to the prothrombotic properties of the device, the biggest clinical challenge is to properly titrate anticoagulant drugs to minimize complications. The risk of bleeding remains a limiting factor for the widespread use of the extracorporeal life support. This case report describes the anesthetic management of a child of adolescent age connected to an extracorporeal membrane oxygenator in whom urgent selective neck dissection was indicated. The aim of this paper is to give a summary of current knowledge and recommendations for the care of patients by anesthesiologists who do not routinely encounter a device for extracorporeal membrane oxygenation in their practice.